Environmental Scanning And Investment Decision Quality: Information Processing Perspective - Nik Muhammad, Nik Maheran (2007)
In a environment scanning becomes critically important when making decisions. particularly investment decisions. Previous research on scanning has proved inconclusive regarding the determinants of scanning behaviors of executives and their subsequent relationships to performance. This study tests empirically the impact of environmental scanning behaviors on investment decision quality and the moderating role of lnformation Processing Capacity in the relationship.